2021
DOI: 10.1021/acssynbio.0c00636
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulin Nanocontainers as Versatile Scaffolds for the Development of Artificial Metabolons

Abstract: The construction of non-native biosynthetic pathways represents a powerful, modular strategy for the production of valuable synthons and fine chemicals. Accordingly, artificially affixing enzymes that catalyze sequential reactions onto DNAs, proteins, or synthetic scaffolds has proven to be an effective route for generating de novo metabolons with novel functionalities and superior efficiency. In recent years, nanoscale microbial compartments known as encapsulins have emerged as a class of robust and highly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 88 publications
0
79
0
1
Order By: Relevance
“…Simply mixing the purified nanocompartment with proteins fused to a SpyCatcher domain covers the nanocompartment surface with the recombinant protein. A similar strategy has been reported using a SpyCatcher fusion on the C terminus of the EncTm encapsulins [83].…”
Section: Shell Engineeringmentioning
confidence: 94%
See 4 more Smart Citations
“…Simply mixing the purified nanocompartment with proteins fused to a SpyCatcher domain covers the nanocompartment surface with the recombinant protein. A similar strategy has been reported using a SpyCatcher fusion on the C terminus of the EncTm encapsulins [83].…”
Section: Shell Engineeringmentioning
confidence: 94%
“…The mutant ∆9Gly2, which generates the largest pore size (~11 Å) [81], showed contradictory results, either with mass transport increased by sevenfold [81] or with minimal differences in the ion flux kinetics [82]. In an unrelated study, the ∆9Gly2 EncTm mutant showed a fivefold increase in the relative performance of a nanoreactor-catalyzed enzyme cascade when compared to wild type EncTm [83]. These results underscore the difficulties inherent to accurately quantifying flux into protein cages and warrant further investigation.…”
Section: Shell Engineeringmentioning
confidence: 97%
See 3 more Smart Citations